INVESTIGATING THE GROUND ENERGY DISTRIBUTION OF PARTICLES PRODUCED IN EXTENSIVE AIR SHOWERS - Wajid, Itab; Al-Rubaiee , Ahmed (Malaysian Journal of Science, 2022)
The energy spectra of particle arrive the ground is a significant observable in the analysis of extensive air showers (EAS). The energy distribution at ground is studied for (12C,56Fe, p, and 28Si ) primary particles with high primary energies (1017, 1018, 1019 and 1020) eV with two zenith angles 0o and 30o. 960 EAS showers are simulated using Monte-Carlo program Aires version (19.04.00) with the models of hadronic interaction (EPOS-LHC, QGSJET-II-04, and Sibyll2.3c). In this study we investigated various secondary particles that arrive the ground and deposit a portion of their energy on ground detectors. The analyzed results show that the distinction in the energy distribution at ground is bigger for primary proton than carbon, iron nuclei, and silicon at higher energies and vertical showers.